Predicting pack-ice seal occupancy of ice floes along the Western Antarctic Peninsula. - Michael J Wethington; Bilgecan Şen; Heather J Lynch (PLoS ONE)
We explore the habitat use of Antarctic pack-ice seals by analyzing their occupancy patterns on pack-ice floes, employing a novel combination of segmented generalized linear regression and fine-scale (∼ 50 cm pixel resolution) sea ice feature extraction in satellite imagery. Our analysis of environmental factors identified ice floe size, fine-scale sea ice concentration and nearby marine topography as significantly correlated with seal haul out abundance. Further analysis between seal abundance and ice floe size identified pronounced shifts in the relationship between the number of seals hauled out and floe size, with a positive relationship up to approximately 50 m2 that diminishes for larger floe sizes and largely plateaus after 500 m2. These patterns provide information on pack-ice seal behavior and, when combined with methods to delineate individual ice floes, can yield predictions on the number of seals likely to be found in each satellite image scene. This work represents another step in the pipeline required to automate the survey of pack-ice seals using satellite imagery, a necessary step towards pan-Antarctic monitoring of these key marine predators.